Surgeon, staff, and patient radiation exposure in minimally invasive transforaminal lumbar interbody fusion: impact of 3D fluoroscopy-based navigation partially replacing conventional fluoroscopy: study protocol for a randomized controlled trial - Hubbe, Ulrich (Trials, 2015)
BACKGROUND: Some symptomatic degenerative conditions of the lumbar spine may be treated with spinal fusion if conservative treatment has failed. The minimally invasive technique of transforaminal lumbar interbody fusion (MIS TLIF) is increasingly used but has been found to generate increased radiation exposure to the patient and staff. Modern three-dimensional (3D) C-arm devices are capable of providing conventional two-dimensional fluoroscopic images (x-rays) as well as 3D image sets for intraoperative navigation. This study was designed to compare the radiation exposure between these two intraoperative imaging techniques in MIS TLIF procedures. METHODS: This study is a randomized controlled trial. Forty participants scheduled to undergo monosegmental MIS TLIF will be recruited and randomly allocated to one of two groups with respect to the applied intraoperative imaging technique: conventional fluoroscopy (FLUORO group) and 3D fluoroscopy-based navigation combined with conventional fluoroscopy (NAV group). Furthermore, patients scheduled to undergo bisegmental MIS TLIF during the recruitment period for monosegmental MIS TLIF will be assessed for eligibility and will be randomly assigned separately. The primary endpoint is the radiation exposure to the surgeon and is measured by dosimeter readings. Secondary endpoints are the radiation exposure to the assistant surgeon, scrub nurse, anesthetist, patient, and C-arm as well as radiation exposure in relation to the body mass index of the patient. DISCUSSION: Results of this randomized study will help to compare the radiation exposure to the operating staff and patient during MIS TLIF procedures using conventional fluoroscopy versus 3D fluoroscopy-based navigation combined with conventional fluoroscopy. Furthermore, recommendations regarding the appropriate use of the investigated intraoperative imaging techniques will be made to improve radiation protection and to reduce radiation exposure. TRIAL REGISTRATION: Registration number of the German Clinical Trials Register: DRKS00004514. Registration date: 11 August 2012.